Propuesta de un manual de seguridad y salud ocupacional en la empresa mineravalentina s.a. del cantón Zaruma, provincia el Oro, periodo 2021 -2022 - Godoy Romero, Martha Vanessa (2022)
The present research work entitled "PROPOSAL OF AN OCCUPACIONAL HEALTH AND SAFETY MANUAL FOR VALENTINA MINING COMPANY S.A. IN ZARUMA CANTON, EL ORO PROVINCE, PERIOD 2021 -2022”, has as main objective to design an occupational health and safety manual for the company MINERA VALENTINA S.A of the Zaruma canton, in order to prevent occupational risks, improve working conditions of work areas and workers performance. The research design was simple descriptive; the techniques used are: the survey applied to the workers, the interview addressed to the manager, and the direct observation guide used in the visits plus physical verifications made to the company, in order to gather information to carry out the proposal in the present work. According to the information collected, it was possible to show that 92% of the workers purchase their personal protection equipment on their own; there are several risk factors to which workers are exposed daily such as: noise, vibrations, inhalation of dust and gases; periodic medical examinations are not carried out on workers. An occupational health and safety manual is proposed, which contains: general regulations of Occupational Health and Safety such as; protection equipment, order and cleanliness, safety in electrical management and driving of vehicles, physical, mechanical, chemical, biological, ergonomic risks, mandatory safety signage in this type of establishment, important concepts within the framework of occupational safety, guidelines for action in cases of emergency within the facilities, training plan on Occupational Safety issues and contingency plan. The legal representative is recommended to grant the necessary resources for the socialization of the manual with the workers.